2012
DOI: 10.1177/147323001204000417
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Superficial Cervical Plexus Block Reduces Postoperative Nausea and Vomiting and Early Postoperative Pain after Thyroidectomy

Abstract: BSCPB with 0.5% ropivacaine administered before surgery can significantly reduce the incidence of PONV and early postoperative pain and also reduce perioperative opioid requirements in thyroidectomy patients undergoing general anaesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 26 publications
4
15
1
1
Order By: Relevance
“…Two recent RCTs have declared that wound infiltration lacks effectiveness for treating pain after thyroidectomy; even in addition of adrenaline [31,32]. The incidences of postoperative nausea and vomiting (PONV) after thyroidectomy ranges from 21.7% up to 84% [12,33]. We have assessed PONV with simplified PONV impact scale and the incidence of clinically important PONV was 27% in block group and 35.1% in non-block group but no statistically significant difference was observed.…”
Section: Discussionmentioning
confidence: 98%
“…Two recent RCTs have declared that wound infiltration lacks effectiveness for treating pain after thyroidectomy; even in addition of adrenaline [31,32]. The incidences of postoperative nausea and vomiting (PONV) after thyroidectomy ranges from 21.7% up to 84% [12,33]. We have assessed PONV with simplified PONV impact scale and the incidence of clinically important PONV was 27% in block group and 35.1% in non-block group but no statistically significant difference was observed.…”
Section: Discussionmentioning
confidence: 98%
“…21,22 Since postoperative pain after START originates from multiple sites and is usually limited to the early postoperative period, 4,5 the proper choice of regional anesthesia with a single-shot technique corresponding to the pain sites is necessary. In the present study, unlike in a previous study, 4 we evaluated the effects of 2 different PNBs separately by comparing VAS scores between the block group and the control group, and we also evaluated the overall postoperative analgesic effect of both blocks after START by measuring the use of rescue analgesics.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24] Several studies have shown that the SCPB not only improves pain control after thyroidectomy and carotid endarterectomy, [18][19][20][21][22][23][24] but it also decreases PONV after thyroidectomy. 18 Nevertheless, we did not find any differences in postoperative opioid consumption between the two groups.…”
Section: Discussionmentioning
confidence: 99%